Peran Perempuan dalam Pembangunan Daerah di Kalurahan Dadapayu, Kapanewon Semanu, Kabupaten Gunungkidul, Provinsi Daerah Istimewa Yogyakarta, Indonesia: Peran Perempuan dalam Pembangunan Daerah di Kalurahan Dadapayu, Kapanewon Semanu, Kabupaten Gunungkidul, Provinsi Daerah Istimewa Yogyakarta, Indonesia - Marista Christina Shally Kabelen; Meila Riska Fitri; Atik Kurniawati (Jurnal Sosiologi Nusantara, 2024)
This research discusses the development of the role of women in the public domain, particularly in village governance in Kalurahan Dadapayu, Kapanewon Semanu, Gunungkidul Regency. The current development of women's roles not only involves dual roles within the household and workplace but also encompasses multiple roles within society, which is an evolving aspect consistently linked to gender equality issues. The aim of this study is to describe the enhancement of women's roles and the development of gender equality in the roles of women in Kalurahan Dadapayu. Additionally, challenges and efforts to strengthen women's presence are also examined in this research. There has been a lot of research conducted that examines gender and patriarchal culture, but the relationship to the role of women in the public sphere is an interesting thing in this research. The research employs a descriptive research method, with sample data selection carried out through purposive sampling. The research findings conclude that there has been progress in empowering women and their roles in public development. Some women have taken on strategic roles, and there are provisions supporting decision-making. Gender equality has been adequately accommodated through the division of domestic roles between spouses in all the sources interviewed.